The Administration of Temporal Goods of Institutes of Consecrated Life: A Juridical-Canonical Perspective - Yohanes Wilson B. Lena Meo; Charles Virgenius Setiawan (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2026)
This study critically examines the canonical discipline governing the administration of temporal goods in Institutes of Consecrated Life. Shifting the focus from a purely administrative-economic perspective, the article posits that the administration of such goods constitutes a profound ecclesial act, intrinsically rooted in the institute’s proper charism. Employing library research and a juridical approach based on the 1983 Code of Canon Law - with particular emphasis on canons 634 -640 and the general provisions of Book V - the study explores how fidelity to the proper charism of the institute serve as the foundational principles for the administration of temporal goods. The findings demonstrate that, given the ecclesiastical nature of these temporal goods, their administration must be strictly ordered toward the specific ends delineated in can. 1254 §2. Furthermore, the analysis highlights that the charism of the institute functions as an indispensable criterion of discernment, ensuring that ensuring that the administration of temporal goods remains inherently coherent with the institute’s identity and its mission in the world.